KUALITAS RUANG TERBUKA PUBLIK LAPANGAN BLANG PADANG KOTA BANDA ACEH - Jumiati Nurdin; Izziah Izziah; Teuku Budi Aulia (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2020)
Public open space is a shared space used by the community for individual or group activities. Quality public open spaces are public spaces that are able to meet needs, protect rights and give meaning to the people who visit them. Blang Padang Field is a tourist zone and public space used by visitors for recreation, sports and selling. Blang Padang as a venue for state ceremonies, religious and military activities. The condition of the physical structure and some of the facilities in it are inadequate as a public space such as a public toilet and seats. Its multi-functional use creates several problems such as parking problems and traffic jams. The method used is quantitative and qualitative using a Likert scale, with descriptive analysis. The data used were observations, questionnaires, and interviews, and data from related agencies. The quality of the Blang Padang Field Public Open Space based on the fulfillment of the needs aspect with a value of 2.97 and the quality of the rights aspect with a value of 2.99 shows a negative response because the average value is below 3, while the quality of the aspects of meaning (meanings) ) got a positive response with an average value of 3.22.